Breastfeeding under siege: a scoping review of flood impacts on lactating mothers - Farah Khalida Abdul Rahman,; Rozita Hod,; Mohd Hasni Jaafar,; Idayu Badilla Idris,; Nurfashareena Muhamad,; Dzulfitree Ahmad,; Nurfatehar Ramly,; Nur Aliya Ayub, (Universiti Kebangsaan Malaysia, 2025)
Floods, as one of the most frequent and devastating natural disasters, create unique challenges for breastfeeding mothers. However, there is limited understanding of the multifaceted impacts of floods on breastfeeding practices. This review aims to examine the impact of floods on breastfeeding mothers and aims to guide disaster response strategies to support maternal and infant health. A scoping review was conducted using the Arksey and O'Malley framework and the PRISMA-ScR methodology. A systematic search of PubMed, Web of Science, and Scopus databases identified eight studies that met predefined inclusion criteria. Eligibility criteria encompassed peer-reviewed articles with quantitative, qualitative, or mixed methods designs. Studies were included if they focused on breastfeeding mothers affected by floods. Eight studies from diverse geographic regions reported significant impacts on breastfeeding practices, including environmental hazard, sociocultural, malnutrition and psychosocial impacts dimensions. Displacement and lack of privacy (e.g., overcrowded shelters, absence of breastfeeding-friendly spaces) disrupted feeding routines. Additionally, maternal malnutrition, stress, and unregulated distribution of formula milk further undermined breastfeeding efforts. Flood disasters pose significant challenges in terms of environmental hazard, sociocultural, malnutrition and psychosocial impacts on breastfeeding mothers, jeopardising maternal and infant well-being. Addressing these issues requires integrated disaster response strategies, including breastfeeding-friendly facilities, nutritional aid, and mental health support. These findings underscore the importance of prioritising breastfeeding in disaster preparedness and response plans to enhance resilience and reduce infant mortality during crises.